Hospitalised exacerbations of chronic obstructive pulmonary disease: adherence to guideline recommendations in an Australian teaching hospital. Issue 4 (8th April 2020) - Sha, Joy; Worsnop, Christopher J.; Leaver, Benjamin A.; Vagias, Christopher; Kinsella, Paul; Rahman, Muhammad A.; McDonald, Christine F.
Abstract: Background: Optimal management of exacerbations of chronic obstructive pulmonary disease (COPD) reduces patient morbidity and healthcare system burden. COPD guidelines, including the Global Initiative for Chronic Obstructive Lung Disease (GOLD) and the COPD‐X Plan, provide evidence‐based recommendations, but adherence in hospital practice is variable. Aims: To examine current practice in management of COPD exacerbations at an Australian teaching hospital and to compare with COPD‐X Plan recommendations. Methods: Data were collected retrospectively from electronic medical records for admissions occurring during 1 May to 31 August 2016, and compared with recommendations from the COPD‐X Plan. Results: A total of 134 patients ( n = 68 females) was admitted for a COPD exacerbation during the study period. Mean age was 75.4 ± 10.2 years and 33.6% were current smokers. Airflow obstruction on spirometry was confirmed in 67.2% (mean forced expiratory volume in 1 s was 53 ± 22% predicted (1.2 ± 0.5 L)). Excellent adherence to the COPD‐X Plan was demonstrated in the ordering of chest radiographs (97%) and electrocardiograms (94%). Supplemental oxygen was appropriately provided to all patients with oxygen saturation of <88%. All patients with confirmed hypercapnic respiratory failure were managed with non‐invasive ventilation. Corticosteroids and bronchodilators were prescribed for the majority of patients. Areas of suboptimal practice included inadequate usage of arterial blood gases, excess supplemental oxygen in the absence of hypoxaemia, over‐prescription of intravenous antimicrobials, low referral rates to pulmonary rehabilitation and insufficient smoking cessation counselling. Conclusions: Level of adherence to guideline recommendations in the management of COPD exacerbations is inadequate and further strategies are required to elevate standards of practice.